Support the Monkey! Tell All your Friends and Teachers

Help / FAQ



Example     Solve for x and y ,

3x - 4y = 10

5x - 3y = 24

Solution :     3x - 4y = 10 . . . (1)

5x - 3y = 24 . . . (2)

From (1), by transposing , 3 x = 4 y + 10

Substituting this value of x in (2)

By multiplying both sides by 3, we get

5 (4y + 10) - 9y = 72

20y + 50 - 9y = 72

11y + 50 = 72

Transposing, 11 y = 72 - 50

1 y = 22

y = 2

Inserting y = 2 in (3) , we get

\ x = 6 is the required solution.

Check : When x = 6 and y = 2

3 x - 4 y = 18 - 8 and 5 x - 3 y = 30 - 6 = 24

Index

7.1 Definition
7.2 Simultaneous Equations
7.3 Inequations (Inequalities)
7.4 Absolute Values

Chapter 8

All Contents Copyright © All rights reserved.
Further Distribution Is Strictly Prohibited.


Search:
Keywords:
In Association with Amazon.com